IMPLEMENTASI NILAI-NILAI KEISLAMAN DALAM MANAJEMEN SEKOLAH DI SMK MUHAMMADIYAH PARAKAN TANGERANG SELATAN - Farsah, Fitriah; Safitri, Indah; Yuliani, Sifa Tiara; Permatasari, Tania Indah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Islamic education aims to shape a whole human being grounded in the values of the Qur'an and Sunnah, yet the practical implementation of Islamic values within school management functions remains rarely examined empirically, particularly at SMK Muhammadiyah Parakan, South Tangerang. This study aims to describe the implementation of Islamic values across school management functions, identify the challenges encountered, and formulate relevant solutions. A descriptive qualitative approach with a case study design was employed. Research subjects were determined through purposive sampling, comprising the principal, vice principal, teachers, education staff, and student council members. Data were collected through participatory observation, in-depth interviews, and document review, then analyzed using the interactive model of Miles and Huberman, with data validity ensured through source and technique triangulation. The findings show that the values of deliberation (musyawarah) and trustworthiness (amanah) are applied in planning; justice and responsibility in organizing; sincerity (ikhlas), excellence (ihsan), and exemplary conduct in actuating; and self-monitoring (muhasabah) and trustworthiness in controlling. The application of these values was found to shape students' discipline and independence, although the school still faces challenges from family habits and social media influence. This study concludes that value-based school management grounded in Islamic principles can support the achievement of holistic educational goals. It is recommended that schools strengthen documentation of deliberative processes and collaboration with parents, and that future research broaden its scope across multiple locations using a mixed-method approach.